534TiPA randomized phase III study of carboplatin plus nab-paclitaxel with or without nintedanib for NSCLC with IPF (J-SONIC). (24th November 2019) - Otsubo, K; Kishimoto, J; Kenmotsu, H; Minegishi, Y; Horinouchi, H; Kato, T; Ichihara, E; Shiraki, A; Atagi, S; Ando, M; Yamamoto, N; Okamoto, I
Abstract: Background: Idiopathic pulmonary fibrosis (IPF) is a fatal lung disease characterized by worsening dyspnea and progressive loss of lung function. Acute exacerbation of IPF is associated with high morbidity and mortality. Several studies have provided evidence of an association between lung cancer and IPF, with a prevalence of lung cancer in IPF patients ranging from 9.8% to 38%. Although the efficacy of nintedanib for IPF has been demonstrated, it has remained unknown whether this agent also reduces the risk of chemotherapy-induced acute exacerbation of IPF. Patients with interstitial pneumonia have been excluded from most prospective clinical trials for NSCLC because of the risk of acute exacerbation, with a few prospective single-arm phase II studies having been reported. In addition, it has been difficult to perform a randomized prospective clinical trial for patients with advanced NSCLC and IPF because of their rarity. Therefore, the optimal chemotherapy regimen for advanced NSCLC with IPF has thus remained unclear. Trial design: Chemotherapy-naïve patients with advanced NSCLC associated with IPF (enrolment target of n = 240) are randomized at a 1:1 ratio to receive four cycles of carboplatin (AUC 6 on day 1) plus nab-paclitaxel (100 mg/m 2 on days 1, 8, and 15) administered every 3 weeks either without (arm A) or with (arm B) nintedanib (150 mg b.i.d., daily), to be followed in arm B by single-agent administration of nintedanib (150 mg b.i.d., daily). The primary end point of the study is time to acute exacerbation of IPF. Study enrolment began in May 2017 and is to continue for 3 years. Legal entity responsible for the study: Isamu Okamoto. Funding: Nippon Boehringer Ingelheim and Japan Agency for Medical Research and Development. Disclosure: All authors have declared no conflicts of interest.